Strategi Dakwah Studi Pemecahan Masalah - Nawawi Nawawi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Dakwah is not only normative understanding of Islamic values, but also understanding human and environment condition as dakwah’s target. In Dakwah activity, we often found many problems as Islamic values bias, poverty, illiteracy, violence, moral decadency, backwardness, etc. These problems cant be solved only with normative teaching. Therefore, proper Dakwah strategy is Dakwah bil hal (practice) or development Dakwah to give solution appropriated with problem faced by umat.